Perspectives on Endogenous Opioids in Birds - Scanes, Colin G.; Pierzchala-Koziec, Krystyna (Frontiers in Physiology, 2018)
The present review summarizes the state of knowledge of endogenous opioids in birds. Endogenous opioid peptides acts in a neuromodulatory, hormonal and paracrine manner to mediate analgesic and other physiological functions. These peptides act through specific G-protein coupled receptors. Opioid receptors consist of a family of four closely-related proteins. The three types of opioid receptors are the mu (MOR or μ), delta (DOR or δ), and kappa (KOR or κ) opioid receptor proteins. The role of the fourth member of the opioid receptor family, the nociceptin or orphanin FQ receptor (ORL), is not clear. The ligands for opioid receptors are: β–endorphin (MOR), Met-enkephalin, Leu-enkephalin (DOR) and dynorphin (KOR), together with probably endomorphins 1 and 2. In spite of long history of research on endogenous opioid peptides, there are no studies of endogenous opioids per se in wild birds and few in poultry species. β-endorphin is present in all birds investigated and there is close agreement between the structures of β-endorphin in different birds. Plasma concentrations of β- endorphin are increased by ether stress in geese. There is evidence that β- endorphin plays a role in the control of luteinizing hormone release in chickens. Met-enkephalin is present in tissues such as the retina, hypothalamus, pituitary gland and adrenals together with circulation of birds. Stresses such as crowding and withholding water increase circulating concentrations of Met-enkephalin in chickens. The structures of chicken dynorphin A and B have been deduced from cDNA. What is missing are comprehensive studies of plasma concentrations and expression of the full array of endogenous opioids in multiple avian species under different situations. Also, what is not known is the extent to which circulating or locally released or intra-cellular Met-enkephalin influence physiological process in birds. Thus, there is considerable scope for investigation of the physiology of endogenous opioids in birds.